Analysis of the current transition readiness of adolescent patients with kidney disease and the factors influencing it - Bai, Shuo; Lv, Maomao; Liu, Jinteng; Liu, Wenjun; Jia, Lili (Frontiers in Pediatrics, 2025)
BackgroundThis study aimed to investigate the transition readiness of adolescent patients with kidney disease to understand their readiness status and ability to transition to adult healthcare and study the influencing factors, to provide a theoretical basis for improving the transition readiness of adolescent patients with kidney disease and developing intervention strategies.MethodsThe study sample was obtained from the follow-up data of the pediatric department at the General Hospital of the Eastern Theater of Operations from December 2024 to January 2025, and patients aged 13–18 years with renal disease were selected as the study subjects. The scores of the Chinese version of the Self-Management and Transitional Readiness Questionnaire were used to determine the readiness status of the study subjects, and binary logistic regression was used to analyze the influencing factors.ResultsA total of 242 questionnaires were distributed, and 12 invalid questionnaires were excluded, resulting in the inclusion of 230 samples for the analysis. Transitional readiness was at a low level in 123 cases (53.48%) and at a medium-high level in 107 cases (46.52%). The results of the binary logistic regression showed that the number of hospitalizations, treatment modalities, place of residence, caregiver's literacy, monthly income, and healthcare payment method were influencing factors for transition readiness in adolescent patients with kidney disease (P < 0.05).ConclusionThe readiness of adolescent patients with kidney disease during their transition to adulthood is not ideal and is affected by a combination of factors related to themselves, their families, and their socioeconomic status. The relevant medical personnel should implement a multidimensional approach and carry out targeted interventions to improve these patients’ readiness for the transition.